转炉倾动装置的优化设计 - 张玉忠; 王铁 (Jixie chuandong)
Tilting device of converter is the most important mechanical equipment on steel-making. A new type multipoint engagement full suspension flexible gearing is introduced. Primal reducer adopts planet differential load balancing mechanism which can make the equipment run more calmly. It is adopted spline axial with suspension simply supported structure between primary and secondary reducer on tilting device of converter. The unstable problem that static variable connection brought between primary and secondary reducer of conventional full suspension tilting device of converter are solved. It is beneficial for raising operation reliability of converter and simplify maintenance.